Clinical effects of specialist and on-call respiratory physiotherapy treatments in mechanically ventilated children: A randomised crossover trial. Issue 4 (December 2015) - Shannon, Harriet; Stocks, Janet; Gregson, Rachael K.; Dunne, Catherine; Peters, Mark J.; Main, Eleanor
Abstract: Objectives: The study investigated treatment outcomes when respiratory physiotherapy was delivered by non-respiratory on-call physiotherapists, compared with specialist respiratory physiotherapists. Design: Prospective, randomised crossover trial. Setting: Paediatric, tertiary care hospital in the United Kingdom. Participants: Mechanically ventilated children requiring two physiotherapy interventions during a single day were eligible. Twenty two physiotherapists (10 non-respiratory) and 93 patients were recruited. Interventions: Patients received one treatment from a non-respiratory physiotherapist and another from a respiratory physiotherapist, in a randomised order. Treatments were individualised to the patients' needs, often including re-positioning followed by manual lung inflations, chest wall vibrations and endotracheal suction. Main outcome measures: The primary outcome was respiratory compliance. Secondary outcomes included adverse physiological events and clinically important respiratory changes (according to an a priori definition). Results: Treatments delivered to 63 patients were analysed. There were significant improvements to respiratory compliance (mean increase [95% confidence intervals], 0.07 and 0.08 ml · cmH2 O −1  · kg −1 [0.01 to 0.14 and 0.04 to 0.13], p  < 0.01, for on-call and respiratory physiotherapists' treatments respectively). Case-by-case, there were fewer clinically important improvements following non-respiratory physiotherapists' treatments compared with the respiratory physiotherapists' ( n  = 27 [43%] versus n  = 40 [63%], p  = 0.03). Eleven adverse events occurred, eight following non-respiratory physiotherapists' treatments. Conclusions: Significant disparities exist in treatment outcomes when patients are treated by non-respiratory on-call physiotherapists, compared with specialist respiratory physiotherapists. There is an urgent need for targeted training strategies, or alternative service delivery models, to be explored. This should aim to address the quality of respiratory physiotherapy services, both during and outside of normal working hours. Clinical Trial Registration number: Clinicaltrials.gov, NCT01999426 .